Correction: First principles study of electronic properties and optoelectronic performance of type-II SiS/BSe heterostructure. (29th March 2023) - Sabir, Shah Saleemullah; Din, H. U.; Alam, Q.; Idrees, M.; Amin, Bin; Khan, W.; Farooq, M.; Nguyen, Cuong Q.; Nguyen, Chuong V.
Abstract : Correction for 'First principles study of electronic properties and optoelectronic performance of type-II SiS/BSe heterostructure' by Shah Saleemullah Sabir et al., New J. Chem., 2023, 47, 4537–4542, ; https://doi.org/10.1039/D2NJ06198H .